ASSESSING THE INCLUSIVITY OF GDP GROWTH AND ITS IMPACT ON POPULATION WELLBEING IN UZBEKISTAN: A STATISTICAL ANALYSIS - Chintemirova Diyora Shuxrat qizi (Insurance market of Uzbekistan, 2026)
This article provides a statistical analysis of the macroeconomic development indicators of the Republic of Uzbekistan for th e period of 2020–2025, specifically focusing on the dynamics of Gross Domestic Product (GDP) growth and its tangible impact on population well-being. The study primarily concentrates on the proportionality between overall economic growth rates and demographic growth trends, as well as the empirical correlation between per capita income and household consumption expenditure. The paper examines the fundamental problem of whether nominal GDP growth effectively ensures a real increase in public welfare, highlighting the inter-sectoral transformation of the economy and the dynamics of household expenditures. Consequently, practical recommendations are proposed to ensure qualitative and inclusive GDP growth and to enhance well-being indicators in the country.